Pengaruh Green Marketing Mix Terhadap Keputusan Pembelian Produk Tupperware - Irsalina, Nadia; Susilowati, Heni (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
Issues regarding the environment have become a problem for the wider community and have resulted in changing consumer preferences to become more inclined to use environmentally friendly products. This is an opportunity for companies to make environmentally friendly products and use more environmentally friendly raw materials. In this study, we analyze and determine the effect of green product, green place, green price, green promotion on purchasing decisions for tupperware products. This type of research is quantitative with the consumer population in the Solo city area. There are 100 respondents, taken by accidental sampling techniquw, and analyzed with the help of the Smart Pls 3.0 application. The result show that the green price and green promotion variables have no significant effect on purchasing decisions. While the green product and green place variables have a significant effect on purchasing decisions. The implication is that the creative industry must continue to improve the quality of environmentally friendly product and knowledge from consumers, so that competitive advantage will be achieved.